THE 21ST CENTURY ADMINISTRATIVE SKILLS OF ADMINISTRATOR AFFECTING TEAMWORK EFFICIENCY OF SCHOOL UNDER NAKHONRATCHASIMA PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Sudthae, Khamphi; Thiamklang, Ong-at; Suriya, Nattapapa; Promdam, Naiyana (Journal for Developing the Social and Community, 2023)
The objectives of this research are to 1) study the skills of administrators in the 21st century under the Nakhon Ratchasima Primary Educational Service Area Office, District 3 2) study the teamwork efficiency of educational institutions under the Nakhon Ratchasima Primary Educational Service Area Office, District 3 and 3) study the relationship between the skills of administrators in the 21st century and the teamwork efficiency of educational institutions under the Nakhon Ratchasima Primary Educational Service Area Office, Area 3. The sample group was teachers under the Nakhon Ratchasima Primary Educational Service Area Office, 3 in the academic year 2022, number of 335 students, obtained by determining the sample size from opening the sample size estimation table of Krejcie and Morgan (Krejcie and Morgan). The tool used in the study was a rating scale questionnaire (Rating scales). Confidence coefficient The whole version was equal to .97. Data were analyzed by averaging. Standard deviation and correlation coefficient The research results found that Skills of administrators of educational institutions under the area office Primary education in Nakhon Ratchasima District 3 is at a high level. The aspect with the highest average was visionary leadership, followed by human relations and creating cooperation) and communicating the mission of the school The teamwork efficiency of school teachers under the Nakhon Ratchasima Primary Educational Service Area Office, Area 3 is at a high level. The aspect with the highest average value was defining roles and job responsibilities, followed by relationships within the group and participation, respectively. The relationship between the skills of school administrators and the teamwork efficiency of educational institutions under the Nakhon Ratchasima Primary Educational Service Area Office, Area 3 is at a high level (r=.889). When considering each aspect, it was found that the pairs The highest correlation was that visionary leadership was related to teamwork efficiency at a high level (r=.869), followed by human relations and cooperation building were related to team efficiency. Work (r=.813) and technology have relatively high relationships with teamwork performance (r=.787).